2014
DOI: 10.3390/molecules19022694
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Substituted Desloratadines as Potent Arginine Vasopressin V2 Receptor Antagonists

Abstract: Twenty-one non-peptide substituted desloratadine class compounds were synthesized as novel arginine vasopressin receptor antagonists from desloratadine via successive acylation, reduction and acylation reactions. Their structures were characterized by 1 H-NMR and HRMS, their biological activity was evaluated by in vitro and in vivo studies. The in vitro binding assay and cAMP accumulation assay indicated that these compounds are potent selective V2 receptor antagonists. Among them compounds 1n, 1t and 1v exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Peaks in 7-8 ppm interval belong to aromatic C-H peaks, peaks in 3-4 ppm belongs to -CH3 in the spectrum of DL. 30,31 Similar spectra were also obtained for the spectra of drug loaded nanoparticle formulations indicating the successful incorporation of drug into the nanoparticles. Physicochemical characterization was undertaken both by DSC and 1 H-NMR measurements.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Peaks in 7-8 ppm interval belong to aromatic C-H peaks, peaks in 3-4 ppm belongs to -CH3 in the spectrum of DL. 30,31 Similar spectra were also obtained for the spectra of drug loaded nanoparticle formulations indicating the successful incorporation of drug into the nanoparticles. Physicochemical characterization was undertaken both by DSC and 1 H-NMR measurements.…”
Section: Resultssupporting
confidence: 62%
“…The combination of both analytical methods proved very suitable to obtain information about the structure of the DL loaded polymers. 31,32 A simple and validated HPLC method was adopted and developed for the determination of DL. The method was validated for accuracy, precision and linearity with reference to the International Council for Harmonisation guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decade, many studies have demonstrated that over-expression of MMP2 and MMP9 plays a vital role in metastatic tumour cells, promoting tumour growth and angiogenesis in the tumour, thereby providing nutrition to the tumour through the newly generated vessels [47]. In animals, MMP2 inhibitors prevented tumor dissemination and the formation of metastases by anti-angiogenic properties [812].…”
Section: Introductionmentioning
confidence: 99%
“…44 A number of compounds with non-benzazepine scaffolds were 45 screened and the phenothiazine scaffold compounds were found to 46 have excellent affinity to V2 receptors. Furthermore, our previous 47 study indicated that the introduction of sulfonyl bond linkage may 48 enhance the biological activity [20,21]. Herein, the synthesis and 49 biological activity of the potent AVP V2 receptor selective agonists 50 based on the phenothiazine scaffold was presented here and the 51 structure-activity relationship (SAR) was discussed.…”
mentioning
confidence: 98%
“…The Sprague-130 Dawley rats were obtained from Shanchuanhong Experimental 131 Animals Co., Ltd (Tianjin, China). The in vitro evaluation was done 132 by the same method we reported previously[20,21]. The in vitro 133 radioligand binding assay was performed to determine the 134 binding affinity of the candidates to human V2 and V1a receptors.142The structures of the target compounds 1a-1y and evaluation of 143 the biological features were summarized inTable 1.…”
mentioning
confidence: 99%